1985
DOI: 10.3758/bf03329806
|View full text |Cite
|
Sign up to set email alerts
|

A theoretical account of the effects of environmental context upon cognitive processes

Abstract: Although the environmental context effect typically refers to superior performance in the context of original learning, this result is not consistently found across all experimental paradigms or instructional sets. Thus far, a precise statement ofthe underlying mechanisms and boundaries of the context effect has been absent from the literature, with the research having focused primarily on the robustness of the effect. The current exposition of a theoretical model and interpretation of the environmental contex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

1989
1989
2004
2004

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…Dalton, 1993;J. E. Eich, 1980;Geiselman & Bjork, 1980;Lockhart & Craik, 1990;Nixon & Kanak, 1985). Smith (1986Smith ( , 1988Smith ( , 1994Smith & Vela, 2001) poetically labelled this the outshining hypothesis, drawing an analogy between the way a bright light outshines and effectively hides any changes in a dim light, and the way high-strength stimulus item cues mask any influence of lower strength EC cues.…”
Section: Outshining: the Relative Cue-strength Hypothesismentioning
confidence: 99%
“…Dalton, 1993;J. E. Eich, 1980;Geiselman & Bjork, 1980;Lockhart & Craik, 1990;Nixon & Kanak, 1985). Smith (1986Smith ( , 1988Smith ( , 1994Smith & Vela, 2001) poetically labelled this the outshining hypothesis, drawing an analogy between the way a bright light outshines and effectively hides any changes in a dim light, and the way high-strength stimulus item cues mask any influence of lower strength EC cues.…”
Section: Outshining: the Relative Cue-strength Hypothesismentioning
confidence: 99%
“…The basic idea that failures to observe context-dependent recognition are caused by differences in relative cue strength has been expressed by a number of authors who have not used the outshining metaphor (e.g., Dalton, 1993; J. E. Eich, 1980; Geiselman & Bjork, 1980; Nixon & Kanak, 1985).…”
mentioning
confidence: 99%
“…However the formation of associations between lexical items through prior experience occurs neurally, it bears an isomorphic relation with the classical conditioning process. Theories about context as a modulator of meaning have been stimulating research in both classical conditioning (Miller & Schactman 1985;Nixon & Kanak 1985) and psycholinguistics (e.g., S. M. Smith et al 1978). It has been found repeatedly that the reported meaning or recognition of linguistic units (phonemes, words, or sentences) is dependent upon the physical or linguistic context in which they are embedded (e.g., Smith et al 1978;Tulving et al 1964;Warren & Warren 1970).…”
Section: )mentioning
confidence: 99%
“…Many classical conditioning studies have found that embedding conditional stimuli in differing stimulus contexts modulates the strength, direction, and "content" of the CR depending upon the subject's prior history in that context (e.g., see a review in Siegel 1983 for rats administered drugs in differing room contexts, and Razran 1971, pp. 136-37, for a study with students who experienced linguistic stimuli in differing room contexts; also see Mackintosh 1983, p. 187, for the role of contextual stimuli in recent conditioned inhibition and contingency theories, and, Nixon & Kanak 1985 for related mathematical formulations).…”
Section: )mentioning
confidence: 99%